Growth and morphogenetic factors in bone induction: role of osteogenin and related bone morphogenetic proteins in craniofacial and periodontal bone repair. - Ripamonti, Ugo; Reddi, A. H. (My University, 1992)
Bone has considerable potential for repair as illustrated by the phenomenon of fracture healing. Repair and regeneration of bone recapitulate the sequential stages of development. It is well known that demineralized bone matrix has the potential to induce new bone formation locally at a heterotopic site of implantation. The sequential development of bone is reminiscent of endochondral bone differentiation during bone development. The collagenous matrix-induced bone formation is a prototype model for matrix-cell interactions in vivo. The developmental cascade includes migration of progenitor cells by chemotaxis, attachment of cells through fibronectin, proliferation of mesenchymal cells, and differentiation of bone. The bone inductive protein, osteogenin, was isolated by heparin affinity chromatography. Osteogenin initiates new bone formation and is promoted by other growth factors. Recently, the genes for osteogenin and related bone morphogenetic proteins were cloned and expressed. Recombinant osteogenin is osteogenic in vivo. The future prospects for bone induction are bright, and this is an exciting frontier with applications in oral and orthopaedic surgery.
Keywords: Bone Morphogenetic Proteins; Alveolar Process/physiology; Osteogenesis